The Influence of Gamification Learning Strategy on Student Activeness in Islamic Cultural History Subject - Yudina Anggita; Nenden Munawaroh; Asep Tutun Usman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine the effect of gamification learning strategies on students’ activeness in Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) learning at Darul Abror Islamic Boarding School. The research employed a quantitative descriptive approach with simple linear regression analysis. The population consisted of all eighth and ninth grade students, totaling 151 students, while the sample included 43 students selected through purposive sampling. Data were collected using observation, interviews, questionnaires, and documentation. Instrument validity was tested using the Pearson Product Moment correlation, and reliability was tested using Cronbach’s Alpha, yielding a reliability coefficient of 0.855, indicating that the instrument was reliable. Data analysis was conducted using SPSS software. The results showed that the gamification learning strategy had a significant effect on students’ activeness, as indicated by a significance value of 0.000 (<0.05). The coefficient of determination (R²) value of 0.352 indicated that gamification strategies contributed 35.2% to students’ activeness, while the remaining 64.8% was influenced by other factors. These findings suggest that gamification learning strategies can be an effective alternative to enhance students’ active participation in Islamic Cultural History learning.